2017
DOI: 10.1111/bjh.15018
|View full text |Cite
|
Sign up to set email alerts
|

The absolute percent deviation of IGHV mutation rather than a 98% cut‐off predicts survival of chronic lymphocytic leukaemia patients treated with fludarabine, cyclophosphamide and rituximab

Abstract: SummaryThe degree of somatic hypermutation, determined as percent deviation of immunoglobulin heavy chain gene variable region sequence from the germline (IGHV%), is an important prognostic factor in chronic lymphocytic leukaemia (CLL). Currently, a cut-off of 2% deviation or 98% sequence identity to germline in IGHV sequence is routinely used to dichotomize CLL patients into mutated and unmutated groups. Because dissimilar IGHV% cut-offs of 1-5% were identified in different studies, we wondered whether no cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 27 publications
1
40
2
1
Order By: Relevance
“…Recently, Jain et al 13 demonstrated in patients treated with the fludarabine, cyclophosphamide, and rituximab regimen that their subsequent course and survival was greatly influenced by the amount of mutations present in the IGHV gene segment. Thus, the higher levels of mutation corresponded to a better outcome, pointing to the potential prognostic relevance of the percentage of IGHV gene mutation as a continuous rather than a dichotomized variable.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Jain et al 13 demonstrated in patients treated with the fludarabine, cyclophosphamide, and rituximab regimen that their subsequent course and survival was greatly influenced by the amount of mutations present in the IGHV gene segment. Thus, the higher levels of mutation corresponded to a better outcome, pointing to the potential prognostic relevance of the percentage of IGHV gene mutation as a continuous rather than a dichotomized variable.…”
Section: To the Editormentioning
confidence: 99%
“…Thus, the higher levels of mutation corresponded to a better outcome, pointing to the potential prognostic relevance of the percentage of IGHV gene mutation as a continuous rather than a dichotomized variable. 13 The particular study design adopted by Jain Table S1). …”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…CLL patients' survival correlated with a continuous increase of IgHV% deviation. The higher the percent deviation, the better was the treatment outcome, suggesting that IgHV% is a continuous and not a dichotomized prognostic variable [11]. Furthermore, the CLL cell gene profile is independent of the IgVH mutation status.…”
mentioning
confidence: 99%
“…In this issue of the British Journal of Haematology, Jain et al () tested the presumption that IGHV somatic hypermutation as a continuous variable is a better predictor of outcome than treating it as a dichotomous variable. Over 500 CLL patients treated with fludarabine, cyclophosphamide and rituximab (FCR) were followed for progression‐free (PFS) and overall survival (OS) based on their pre‐treatment IGHV percentage.…”
mentioning
confidence: 99%